Meta-Analysis the Effect of Obesity on Polycystic Ovary Syndrome and Anemia in Women of Reproductive Age - Tsaqifah, Nabila Aulia; Adriani, Rita Benya; Murti, Bhisma (Journal of Maternal and Child Health, 2021)
Background: Obesity in women of reproductive age is a nutritional problem that needs attention because obesity affects other health problems, especially problems of nutrient absorption and reproductive health. This needs special attention considering that the health of women of reproductive age has a major influence on the quality of future generations. The purpose of this study was to estimate the magnitude of the effect of obesity on the possibility of polycystic ovary syndrome (PCOS) and anemia in women of reproductive age. Subjects and Method: Systematic review and meta-analysis. The data of this study used a research research design obtained from the databases of Google Scholar, PubMed, BMJ, ScienceDirect, SpingerLink, and Sage. The inclusion criteria used were full paper, cross-sectional and cohort study designs with reported results adjusted odds ratio (aOR). Article searches were performed using the PICO model. Population= women of reproductive age, Intervention= Obesity, Comparison= not obese, Outcome= anemia and PCOS. Articles were collected using PRISMA diagrams and analyzed using the Review Manager application (RevMan5.3). Results: A total of 10 articles on the relationship of obesity with anemia and 4 articles on the relationship of obesity with PCOS. Studies show that obesity reduced the risk of anemia compared to normal weight in women of reproductive age (aOR= 0.73; 95% CI= 0.63 to 0.84; p<0.001). Obesity increased the risk of PCOS 1.21 times compared to women with normal weight (aOR= 1.21; 95% CI= 1.00 to 1.48; p= 0.050). Conclusion: Obesity reduces the risk of anemia. Obesity increases the risk of PCOS in women of reproductive age.